2020
DOI: 10.1038/s41467-019-13883-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin-dependent M cell self-regulation balances gut infection and immunity

Abstract: Microfold cells (M cells) are responsible for antigen uptake to initiate immune responses in the gut-associated lymphoid tissue (GALT). Receptor activator of nuclear factor-κB ligand (RANKL) is essential for M cell differentiation. Follicle-associated epithelium (FAE) covers the GALT and is continuously exposed to RANKL from stromal cells underneath the FAE, yet only a subset of FAE cells undergoes differentiation into M cells. Here, we show that M cells express osteoprotegerin (OPG), a soluble inhibitor of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…RANKL has been regarded as the master osteoclastogenic factor and a key determinant of periodontal/periapical lesion progression (Yuan et al 2011; Francisconi et al 2018; Alvarez et al 2019). However, the RANK (receptor activator of nuclear factor kappa B)/RANKL/OPG system plays important roles in the regulation of the immune system, modulating lymphoid organ microenvironments and influencing immune response outcomes (Lin et al 2016; Kimura et al 2020). In peripheral tissues, RANKL exerts an immunoregulatory role by modulating the phenotype and function of dendritic cells (DCs) (Williamson et al 2002; Loser et al 2006; Izawa et al 2007; Lin et al 2016).…”
Section: Rankl As a Double-edged Sword: Its Dual Role In Triggering Lmentioning
confidence: 99%
See 1 more Smart Citation
“…RANKL has been regarded as the master osteoclastogenic factor and a key determinant of periodontal/periapical lesion progression (Yuan et al 2011; Francisconi et al 2018; Alvarez et al 2019). However, the RANK (receptor activator of nuclear factor kappa B)/RANKL/OPG system plays important roles in the regulation of the immune system, modulating lymphoid organ microenvironments and influencing immune response outcomes (Lin et al 2016; Kimura et al 2020). In peripheral tissues, RANKL exerts an immunoregulatory role by modulating the phenotype and function of dendritic cells (DCs) (Williamson et al 2002; Loser et al 2006; Izawa et al 2007; Lin et al 2016).…”
Section: Rankl As a Double-edged Sword: Its Dual Role In Triggering Lmentioning
confidence: 99%
“…While currently available studies usually focus on DC activation by bacteria or their products, additional signaling molecules, such as RANKL, can also modulate DC activity. In previous studies, RANKL-stimulated DCs were shown to enhance a T-cell effector response, albeit recent evidence points toward a prevalent imprint of an immunoregulatory phenotype in DCs by RANKL (Williamson et al 2002; Loser et al 2006; Izawa et al 2007; Kimura et al 2020). In an experimental periapical lesion model, as expected, RANKL inhibition limited the osteolytic response while also impairing the natural immunoregulatory process over time (Francisconi et al 2018).…”
Section: Rankl As a Double-edged Sword: Its Dual Role In Triggering Lmentioning
confidence: 99%
“…Cluster 13 displayed elevated expression of POU Class 2 Homeobox 3 (pou2f3), which is a lineagespecifying transcription factor for tuft cells in mice (92), as well as Sprouty 2 (spry2) which is regulates differentiation of goblet and tuft cells in mice (93). Interestingly, cells in cluster 13 also displayed elevated expression of genes known to be involved in the development of antigen-sampling microfold cells (M-cells) in the mammalian intestine including SRY-Box Transcription Factor 8 (sox8b) (94), TNF Receptor Superfamily Member 11a (tnfrsf11a; also known as RANK) (95), and its conserved paralog tnfrsf11b (also known as Osteoprotegerin) which acts as a decoy receptor for RANK ligand (96). Tuft cells and M-cells are considered to be distinct differentiated cell types in the mammalian gut, but these zebrafish cells in cluster 13 appear to display conserved markers of both cell types.…”
Section: Figures Andmentioning
confidence: 99%
“…Flagellin stimulates host cells through binding to Toll-like receptor 5 (TLR5). The lack of significant induction of Ccl20 and M cell-related gene expression in enteroids after flagellin treatment was further supported by the absence of Tlr5 mRNA expression in deep CAGE sequence data from GP2+ M cells, FAE and RANKL-stimulated enterocytes from the FANTOM consortium ( Figure 6G ; (Forrest, 2014)), and in published mRNA-seq data from isolated GP2+ M cells ( Figure 6H ; (Kimura et al, 2020)). These data suggest that the effect of flagellin on M cell density in vivo is not mediated through direct TLR5-mediated stimulation of enterocytes or immature M cells in the FAE.…”
Section: Resultsmentioning
confidence: 71%
“…Statistical differences determined by two-way ANOVA. (G-H) Comparison of Tlr5 and Gp2 mRNA expression (G) in individual cell populations in deep CAGE sequence data from the FANTOM5 project of the FANTOM consortium (Forrest, 2014), and (H) in published mRNA-seq data from isolated GP2+ M cells (GSE108529; (Kimura et al, 2020)).…”
Section: Resultsmentioning
confidence: 99%